Pengaruh pemberian peregangan (stretching) terhadap penurunan keluhan nyeri pinggang dan nyeri punggung bawah (low back pain) pada pekerja bagian menjahit cv.vanilla production susukan semarang - Okananto, Adi, Tarwaka, PGDip Sc, M.Erg, Dr. Suwadji, M.Kes (2014)
Low back pain is a musculoskeletal disorder that is on the lower back region caused by various diseases and bodily activity that is less good. The provision of such movements stretching that can reduce muscle complaints are stretching movement or stretching. The purpose of this study was to determine The Effect of Giving Stretching exercises to the decline in complaints Low Back Pain And Lower Back Pain of the Workers In The Sewing CV.Vanilla Production Susukan Semarang. This research method used Non-Equivalent Control Group. The subjects were 34 female sewing workers by using totalsampling. Statistical test with a significant level (α=0,05) using test Man-Whitney. Statistical test results obtained pre-test after p-value (0,293>0,05) so there was no difference in low back pain and lower back pain on the control and treatment groups. Then, obtained after post-test p-value (0,000≤0,05) so there a significant low back pain and lower back pain average difference between the control and treatment groups. It can be concluded there are effect of stretching for sewing workers againts low back pain and lower back pain complaints in the treatment group.